Intermittent catheter users' symptom identification, description and management of urinary tract infection: a qualitative study. Issue 9 (3rd September 2017) - Okamoto, Ikumi; Prieto, Jacqui; Avery, Miriam; Moore, Katherine; Fader, Mandy; Sartain, Samantha; Clancy, Bridget
Abstract : Objectives: To elucidate the views of intermittent catheter (IC) users regarding urinary tract infection (UTI) symptom presentation, terminology for describing signs and symptoms, the cause of UTI and management strategies. Design: Qualitative study with semi-structured interviews. The transcribed text was analysed thematically. Setting: 12 general practitioner (GP) surgeries in Hampshire and Dorset, UK. Participants: A convenience sample of 30 IC users, aged over 18, using IC for at least 3 months who had at least one self-reported UTI since starting IC. Results: Participants reported a variety of signs and symptoms, such as urine cloudiness and smell, as indicators of UTI. The terms used often differed from those in the modified National Institute on Disability and Rehabilitation Research (NIDRR) symptom set. IC users had difficulty distinguishing possible UTI symptoms from those of their comorbidities. They expressed uncertainty about the cause of UTI, often attributing it to poor hygiene and lifestyle behaviours. Whereas some viewed UTI as an expected consequence of IC use that could be self-managed, others felt more concerned and were more reliant on their GP for support. A range of management strategies was described, including drinking more fluids, increased attention to personal hygiene and self-medicating with antibiotics. Conclusions: There is uncertainty among IC users about UTI signs and symptoms and when to seek help. Individual accounts of UTI fitted generally within the modified NIDRR descriptors but adopted less technical and more 'lay' language. IC users' descriptions of UTI signs and symptoms can lack precision, owing partly to the presence of underlying health conditions. This, together with differing levels of concern about the need to seek help and self-medication with antibiotics, presents challenges for the GP. This study provides the basis for developing a self-help tool which may aid identification of UTI and enhance communication with healthcare professionals.